Impact of Disease Factors of Patients with Psoriasis and Psoriatic Arthritis on Biologic Therapy Switching: Real-World Evidence from the CorEvitas Psoriasis Registry - Philip J. Mease; Andrew Blauvelt; Adam P. Sima; Silky W. Beaty; Robert Low; Braulio Gomez; Marie Gurrola; Mark G. Lebwohl (Adis, Springer Healthcare, 2024)
Abstract Introduction Patients with psoriasis (PSO) and psoriatic arthritis (PsA) may frequently switch biologic therapies over the course of treatment because of symptom variability and individual responses. Real-world studies analyzing patient characteristics and clinical factors associated with biologic switching are limited. Methods This longitudinal cohort study used real-world data from the CorEvitas Psoriasis Registry to evaluate the relationship between associated disease factors and biologic switching among patients with PSO and PsA in the United States (US) and Canada following initiation of a biologic. Patients were evaluated between April 2015-August 2022. Combinations of disease severity (as measured by Psoriasis Area Severity Index [PASI]) and Dermatology Life Quality Index (DLQI) as a measure of health-related quality of life (HRQoL) were assessed, and the association with time to switching was calculated using Cox proportional hazards regression modeling. Results Among 2580 patient-initiations (instances of patients initiating a biologic), 504 (19.5%) switched biologics within 30 months of initiation. Switching was more frequent when either PASI > 10 or DLQI > 5 compared with PASI ≤ 10 or DLQI ≤ 5 at follow-up. Patients with higher skin involvement (PASI > 10) and impact on HRQoL (DLQI > 5) were 14 times more likely to switch (hazard ratio = 14.2, 95% confidence interval: 10.7, 18.9) than those with lower skin involvement (PASI ≤ 10) and HRQoL (DLQI ≤ 5). Conclusions Patients with PSO and PsA treated in a real-world dermatology setting with substantial disease factors following biologic initiation were more likely to switch therapies. Those with PASI > 10 and DLQI > 5 switched more frequently than those with PASI ≤ 10 and DLQI ≤ 5.